PENGARUH PENAMBAHAN RAGI TAPE DAN WAKTU FERMENTASI TERHADAP KARAKTERISTIK CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO - Dwi Satryo, Bangkit; Arnata, I Wayan; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 1 (2015): Maret)
This study purpose were (1) to determine the effect of “ragi tape” inoculum additional and fermentation time on the characteristics of watery sweating and (2) to determine the best treatment to obtain potential liquid pulp as material fermentation vinegar. The result showed that the treatment of fermentation time significantly affects to the yield, and pH cocoa pulp beans, and affects to total acid degree and total acetic acid cocoa pulp beans, meanwhile the treatment of additional yeast concentration and the interaction treatment A and B does not affect to the yield, pH, total acid degree and total acetic acid cocoa pulp beans. The best treatment as material vinegar fermentation there was in one day fermentation until three days fermentation was suggestion with opinion, that degree of acetic acid and yield of liquid pulp was filled the condition to material of fermentation vinegar
Keywords: 27,